2017
DOI: 10.1016/j.jchf.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Center Left Ventricular Assist Device Volume on Outcomes After Implantation

Abstract: Center volume correlates with post-VAD survival, with worse survival noted at very-low volume centers. These findings suggest that current U.S. VAD center standards warrant reconsideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 18 publications
3
42
0
1
Order By: Relevance
“…Several pediatric cardiology studies have noted improved surgical outcomes in higher‐volume centers, particularly among more complex procedures such as the Norwood operation 15,16 . Similarly, studies in adult VAD patients found a correlation with higher post‐VAD mortality at low‐volume centers, defined as ≤10 VADs per year, compared with high‐volume centers (>50 implants/year) 17 . In pediatrics, most centers are low‐volume, with 74% of our survey respondents at centers with ≤10 VADs/year and 78% of respondents at centers with ≤5 SV implants over the previous 3 years.…”
Section: Discussionmentioning
confidence: 93%
“…Several pediatric cardiology studies have noted improved surgical outcomes in higher‐volume centers, particularly among more complex procedures such as the Norwood operation 15,16 . Similarly, studies in adult VAD patients found a correlation with higher post‐VAD mortality at low‐volume centers, defined as ≤10 VADs per year, compared with high‐volume centers (>50 implants/year) 17 . In pediatrics, most centers are low‐volume, with 74% of our survey respondents at centers with ≤10 VADs/year and 78% of respondents at centers with ≤5 SV implants over the previous 3 years.…”
Section: Discussionmentioning
confidence: 93%
“… 5 Similarly, hospital volume is strongly associated with survival after the placement of left ventricular assist device (LVAD). 6 Emergency surgical procedures have a disproportionately high risk for mortality and an important question is whether centers with different emergency surgery volumes have equivalent outcomes. The published literature is not definitive on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the variables that were found to be predictive in these models have previously been recognized as high risk factors in separate analysis. (1315) Rather than trying to combine a multiplicity of factors by using a weighted summation, Bayesian models provide a dynamic incorporation of many variables, yielding a more robust ROC value than previously published scores. (6, 11) The 90-day and 1-year HMRS stratifications had AUC of 61% and 59%, respectively, whereas the Bayesian 90-day and 1-year predictions exhibited AUC of 71% and 70%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a non-patient related variable would be the number of LVAD implants performed at a site annually, which has been shown to impact patient outcomes. (13) The final BN models included both non-modifiable/historical variables (such as patient age and surgical intervention history) and modifiable variables (such as nutritional assessment, renal function etc.). We recognize that long-term mortality post LVAD implantation is likely more influenced by post-operative adverse events (such as stroke, infections, right ventricular failure etc.)…”
Section: Discussionmentioning
confidence: 99%